PENGARUH CITRA TOKO TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN DI YOGYAKARTA - Dwi Wahyu Pril Ranto (Jurnal Bisnis, Manajemen, dan Akuntansi, 2017)
The purpose of this study is to examine the effect of store image on customer satisfaction and customer loyalty. This research was conducted at Java Market store located in Kasihan Bantul, Yogyakarta. The sample in this research is the customer who has come to Java Market store with the frequency of arrival at least twice. This study used purposive sampling, the sample is taken based on the selection of members of the population on the basis of certain considerations. Based on hypothesis test results can be concluded that the image store has a positive influence on customer satisfaction, customer satisfaction has a positive effect on customer loyalty and store image have a positive effect on customer loyalty.Keywords: store image, customer satisfaction, customer loyalty